INPOP: evolution, applications, and perspectives. (5th March 2015) - Fienga, A.; Laskar, J.; Manche, H.; Gastineau, M.; Verma, A.
Abstract: The INPOP ephemerides have undergone several improvements since the last INPOP10a release (Fienga et al .2011 ). Improvements in the asteroid mass determinations have been made and the effect of the solar corona has also been investigated (Verma et al . 2012). Since 2010 and INPOP10a, in anticipation to IAU resolution B2, the au is fixed in the INPOP construction while the mass of the Sun is fitted. Descriptions of tests of general relativity made with INPOP10a are recalled here. Perspectives about Messenger data analysis and new gravity tests are finally introduced.